Cricketing Insights Unveiled: Python-Based Information Extraction from IPL - Kubra Bashir; Afsheen Maroof; Fatima Maqbool; Kiran Bashir; Syeda Iqra Hassan (JISR on Computing)
In today’s data-driven world, the importance of data analytics is growing exponentially. Data analysis aims to extract valuable insights from large datasets and facilitate informed decision-making. It plays a pivotal role across various fields, including healthcare, business, education, sports, and entertainment. Utilizing data science and Python programming, this study delves into analyzing raw IPL data to uncover actionable insights. Cricket holds a special place in the hearts of fans worldwide. This article focuses on extracting meaningful insights from raw IPL data compiled in Excel sheets, encompassing details like team performance, seasons, match dates, venues, players, toss outcomes, and umpire decisions. Each attribute was meticulously analyzed to derive insights that can aid in predicting match outcomes and enhancing player performance.